2009
DOI: 10.1111/j.1600-0536.2008.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

There is an association between contact allergy to aluminium and persistent subcutaneous nodules in children undergoing hyposensitization therapy

Abstract: There was a statistically significant association between contact allergy to aluminium and persistent subcutaneous nodules in children who had had hyposensitization therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 20 publications
(45 reference statements)
3
69
1
Order By: Relevance
“…[189][190][191][192] For aluminum hydroxide containing SCIT products, granulomas have been described from a foreign body reaction mainly caused by incorrect intradermal administration as well as contact allergic reactions, new onset of protein contact dermatitis, or a vasculitis inflammatory reactions have been reported. [193][194][195] If these reactions to SCIT occur, treatment with another aluminum hydroxide-free product is preferred (Grade D). 11 …”
Section: Scitmentioning
confidence: 99%
“…[189][190][191][192] For aluminum hydroxide containing SCIT products, granulomas have been described from a foreign body reaction mainly caused by incorrect intradermal administration as well as contact allergic reactions, new onset of protein contact dermatitis, or a vasculitis inflammatory reactions have been reported. [193][194][195] If these reactions to SCIT occur, treatment with another aluminum hydroxide-free product is preferred (Grade D). 11 …”
Section: Scitmentioning
confidence: 99%
“…71 Patch tests should be read after 3 or 4 days and after 1 week. 72 An itching granuloma and a positive epicutaneous test are illustrated in Figures 3 and 4.…”
Section: Local Aluminum Reactionsmentioning
confidence: 99%
“…The development of pruritic nodules at hyposensitization therapy injection sites has been attributed to aluminum. In one study, 8 of 37 children who underwent this therapy showed a contact allergy to aluminum (Netterlid et al, 2009). Iron is considered a rare cause of allergic contact dermatitis, though one case describing a 7-year-old boy with an iron allergy related to his orthopedic prosthesis has been reported .…”
Section: Other Metalsmentioning
confidence: 99%